5α,6α-Ep-oxy-7-norcholestan-3β-yl acetate - Andrade, L. C. R. (2012)
The title cholestan, C(28)H(46)O(3), was prepared by epoxidation of 7-norcholest-5-en-3β-yl acetate and crystallized by slow evaporation from an ethano-lic solution. All rings are trans fused. The 3β-acetate and the 17β-cholestane side chain are in equatorial positions. The mol-ecule is highly twisted due to its B-nor characteristic. A quantum chemical ab-initio Roothaan Hartree-Fock calculation of the equilibrium geometry of the isolated mol-ecule gives values for bond lengths and valency angles in close agreement with the experimental ones.